Relative performance of two Nile tilapia (Oreochromis niloticus Linnaeus) strains in Egypt: The Abbassa selection line and the Kafr El Sheikh commercial strain - Ibrahim, A.N.; Abou Zaid, M.Y.; Hooi Ling Khaw; El-Naggar, G.O.; Ponzoni, R.W. (Hindawi Limited, 2013)
The Abbassa selection line (developed by selective breeding) and the Kafr El Sheikh commercial strain (widely used in Egypt), both Oreochromis niloticus, were compared at two stocking densities (two and four fish m−2). Harvest weight, length, depth, width and head length were recorded. The Abbassa line showed a superior harvest weight (28 per cent) over the Kafr El Sheikh strain. Males were heavier than females, but the between-sex difference was greater in the commercial than in the Abbassa line (39 and 31 per cent respectively). Females in the Abbassa line grew almost as fast as males in the commercial line. Both strains grew faster at the lower density, and the percentage reduction in harvest weight at the higher density was about the same for both strains (27 per cent). The advantage of the Abbassa line was 28 per cent at both densities. Both strains had a similar survival rate (approximately 80 per cent) during the grow-out period. We conclude that the Abbassa line is ready for release to the tilapia industry in Egypt. Further evidence is being sought in currently underway on-farm evaluations. Measures should be taken to ensure the long-term viability of the Abbassa line.